Mapping Customer Delight by Using a Surprise Model - Dubey, Prince; Bajpai, Naval; Guha, Sanjay (Indian Journal of Marketing, 2016)
Marketing is full of vivacious thoughts and surprises. Marketers are exploring the thought of creating surprises to achieve a competitive advantage in the business market. The customers are key stakeholders in any business. The present study tested a model containing surprises and 10 antecedents creating customer delight. The study was conducted with a motivation to find out an avenue of creating surprises leading to a variety of delight outcomes. The present study tried to classify customer affective responses in three broad categories as low, moderate, and high. Differences in categories were checked for the purpose of basic classification, and discriminant function analysis was conducted for identifying predictor surprise variables discriminating power for such classification. The results of the study confirmed the key role of add-on features, humor, schema discrepancy, and perceived firm expertise in deciding the classification. For marketing insights, the profile of each category was designed by using vector diagrams. Store environment and product appearance were found to be relatively important predictor vector variables on the basis of magnitude calculation. The present study would be useful for the marketers in taking the decisions related to products and promotions for creating delightful customers.